Kandungan Nutrisi, Aktivitas Antioksidan dan Karakter Sensori Liang Teh Pada Berbagai Penambahan Sari Jeruk Sambal Pada Liang Teh - Yohana Sutiknyawati Kusuma Dewi (Universitas Tanjungpura, 2023)
Tea is a popular drink consumed in Pontianak City, Indonesia. One type of tea served commercially in Pontianak City, Indonesia, consists of a mixture of muje leaves, pineapple shells, oregano leaves, aloe vera skin, pandan leaves as a tea ingredient and secang as a tea ingredient, with a certain ratio. The trend of flavors in tea with a typical Pontianak ocitrus flavor such as Citrus amblycarpa that it “jeruk sambal” is locally name, is interesting to study. The purpose of this study was to determine the nutritional content, antioxidant activity and sensory characteristics of tea leaves in various additions of orange and chili sauce. There were seven concentration formulations of adding chili orange juice (0 ; 0.5 ; 1.0 ; 1.5; 2.0 ; 2.5 and 3.0) % to the tea liang formula used in this study. The observed variables were vitamin C content, pH, antioxidant activity and sensory characteristics. The results showed that the content of vitamin C, pH and antioxidant activity were affected by the concentration of the addition of orange chili juice. The content of citamin C ranged from 11.88 ± 0.21 to 23.41 ± 0.34 mg/100 ml, the pH ranged from 4.16 ± 0.26 to 6.52 ± 0.12 and the resulting activity was 45 .61 ± 0.41 to 60.03 ± 1.41 % for DPPH radical inhibition. The sensory characteristics of the resulting tea burrows do not affect the aroma but affect the color and taste. Based on the results of the study it was found that the addition of 0 to 3% chili orange juice to the tea liang formulation could increase the vitamin C content, lower the pH and antioxidant activity but only affect the color and taste and not affect the aroma.